Guidance from the Seerah: Addressing Modern Marital Challenges with Traditional Wisdom (Al-Aasar, 2025)
This paper examines the timeless relevance of the Prophet Muhammad’s (Peace Be Upon Him) marital principles attached in compassion, justice, and emotional intelligence as a framework for addressing the evolving challenges of contemporary Muslim families. Drawing on Seerah-based teachings, it explores how Prophetic guidance on communication, mutual respect, shared responsibility, and conflict resolution can serve as an ethical and practical foundation for marital harmony. The study highlights that modern factors such as digital distractions, changing gender roles, financial stress, and the weakening of traditional family structures contribute to increasing instability in marital relationships. By integrating the Prophet’s (PBUH) values of moderation, empathy, and fairness into counseling, education, and legal systems, Muslim societies can develop sustainable solutions that promote gender equity, emotional well-being, and familial peace. Ultimately, the research argues that revitalizing Seerah-inspired marital ethics not only strengthens spousal relationships but also reinforces broader social stability in an era marked by technological and cultural transformation.